Child Sexual Abuse, Alcohol and Other Drug use and the Criminal Justice System: The Meanings of Trauma in Survivor Narratives for a National Royal Commission. (January 2023) - Treloar, Carla; Idle, Jan; valentine, kylie
Adverse childhood experiences, including childhood sexual abuse, have significant immediate and lifelong effects including higher risks of alcohol and other drug use and contact with the criminal justice system. The concept of trauma to describe adverse experiences and later behaviours provides potential to reshape prevention and responses for victims. We draw on survivor accounts to a national enquiry, the Australian Royal Commission into Institutional Responses to Child Sexual Abuse, to examine the ways in which trauma is narrated in adverse childhood experiences, alcohol and other drug use and contact with the criminal justice system, and how trauma is interpreted by others in the context of policy and legal findings. These accounts showed damaging and unjust experiences of childhood, which were compounded by subsequent contact with the criminal justice system. Trauma seems to be important to both the experienced narrated by survivors and the synthesising of these experiences into narratives. National enquiries play important roles in listening to survivors and advocating for reform. There is a risk, however, that they will fail to result in substantive change, and function primarily as a forum for bearing witness to trauma, but not preventing it.